Development of a Novel Peptide Nucleic Acid Probe for the Detection of Legionella spp. in Water Samples - Montserrat Nácher-Vázquez; Ana Barbosa; Inês Armelim; Andreia Sofia Azevedo; Gonçalo Nieto Almeida; Cristina Pizarro; Nuno Filipe Azevedo; Carina Almeida; Laura Cerqueira (Microorganisms, 2022)
Legionella are opportunistic intracellular pathogens that are found throughout the environment. The Legionella contamination of water systems represents a serious social problem that can lead to severe diseases, which can manifest as both Pontiac fever and Legionnaires’ disease (LD) infections. Fluorescence in situ hybridization using nucleic acid mimic probes (NAM-FISH) is a powerful and versatile technique for bacterial detection. By optimizing a peptide nucleic acid (PNA) sequence based on fluorescently selective binding to specific bacterial rRNA sequences, we established a new PNA-FISH method that has been successfully designed for the specific detection of the genus Legionella. The LEG22 PNA probe has shown great theoretical performance, presenting 99.9% specificity and 96.9% sensitivity. We also demonstrated that the PNA-FISH approach presents a good signal-to-noise ratio when applied in artificially contaminated water samples directly on filtration membranes or after cells elution. For water samples with higher turbidity (from cooling tower water systems), there is still the need for further method optimization in order to detect cellular contents and to overcome interferents’ autofluorescence, which hinders probe signal visualization. Nevertheless, this work shows that the PNA-FISH approach could be a promising alternative for the rapid (3–4 h) and accurate detection of Legionella.